Applying spatial analysis to assess crop damage a case study of the Pakistan 2022 floods - Yamano, Takashi; Gumma, Murali Krishna; Panjala, Pranay; Ul Haq, Nauman; Fahad, Muhammad; Sato, Noriko; Arif, Babur Wasim; Saeed, Umer (Mandaluyong City, Metro Manila Asian Development Bank, 2024)
Pakistan is highly flood-prone and faces a growing risk of water-related disasters due to predicted impacts of climate change. From 1950 to 2021, each of the major floods claimed more than 400 lives in Pakistan, except the 1950 flood that claimed at least 2,000 lives. The latest flood in 2022 resulted in 1,678 deaths, which included 555 children. The Food and Agriculture Organization of the United Nations estimates that 55,000 square kilometers of land were flooded. This report presents how spatial analysis could be used to assess flood damage to agricultural production by applying the analysis to the 2022 Pakistan floods. It recommends that spatial analysis capacity should be established within government agencies to ensure better preparedness for mitigating damages of future water-related disasters. Using spatial analysis and a spectral mapping technique, the 2022 flood damage was assessed for four periods during June–September 2022 in Pakistan. The assessment conducted during the first half of September 2022 indicated that about 15% of crop areas were modestly or severely damaged. The accuracy of the technique was verified by cross-checking with data gathered at the actual locations on the ground. Subsequently, a monthly damage assessment system has been established and is circulating monthly reports to government agencies to help them prepare for future floods and other crop damage. Spatial mapping can also be used to assess the impact of crop disease, pest infestations, drought, and others, and to inform policy makers and decision makers about situations pertinent to the national food supply, export earnings, and crop insurance. Spatial mapping can provide estimations of crop health for a wider area and do so faster than ground estimations, which require large amounts of resources, such as labor and transport, and are difficult to implement after floods or other natural hazards.

Key recommendations to facilitate the use of technology to enhance crop monitoring are as follows: (i) increase the number of geographic information system and remote sensing specialists in relevant government agencies such as crop reporting services and statistics offices; (ii) integrate the use of spatial analysis into statistical reporting systems to improve their accuracy and timeliness. The spatial analysis can provide preliminary results that can be verified by field observations; (iii) familiarize policy makers with and enable them to interpret spatial analysis results to help them make more effective decisions. Circulate periodic spatial analysis reports among policy makers to earn their trust in the analysis; and (iv) plan policy actions for early detection of crop damage, rapid field verifications, mobilization of adequate financial and material resources, and effective communications with affected populations. Images from spatial analysis can be released through media or posted on government websites.
Keywords: Agriculture and natural resources -- Pakistan; Climate change -- Pakistan